Edukasi Kesehatan Mental Dan Emosional Bagi Kader Pencak Silat Tapak Suci - Sulasikin Sahdi Kadir; Haerul Ikhsan; Ardin Abdul Gani (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Mental health is a crucial aspect in physical activities such as pencak silat, although it often receives less attention, even though mental balance plays an important role in optimal performance. This community service aims to improve Pencak Silat Tapak Suci Pimwil XXXI cadres' understanding of mental health and relaxation techniques that can be applied in training. The methods used include lectures on mental health, relaxation technique practice sessions, and group discussions, with evaluations to measure participant understanding and the effectiveness of the methods applied. The results showed that 60% of participants considered the program's objectives very clear, and 50% felt the material presented was satisfactory; most participants considered the delivery method effective in improving their understanding. In conclusion, this program succeeded in increasing cadres' awareness and knowledge about mental health, and it is recommended to be continued and developed further with an emphasis on integrating relaxation techniques into pencak silat training routines to achieve better mental balance.